Pengaruh Deskripsi Pekerjaan Dan Gaya Kepemimpinan Terhadap Motivasi Kerja Pegawai Bappeda Kabupaten Tabanan - Astiari, Putu Trisna Desy; Sudarma, I Nyoman (E-Jurnal Manajemen, 2014)
This research has purposes to know the influence of job descriptions and leadership style on work motivation of the employees. T he number of samples was taken as much as 64 employees . Data collections were assisted by literature study, distribution of the questionnaire, and observation. The t echnic of analysis was used multiple linear regression. Based on the analysis result, there was found if job descriptions and leadership style has significant affect simultaneously and partially to the work motivation of employees in agency for regional development at Tabanan Regency. This thing show clearly if in job descriptions the leader put down feasible facilities to finish all projects will more increasing work motivation in order to do that, and if the leader have more awareness of responsibility to complete facilities of the employees matching with their work needs it could make good enhancement, especially in work motivation. Key words: job descriptions, leadership style, work motivation Normal 0 false false false EN-US X-NONE X-NONE
Keywords: Key words: job descriptions, leadership style, work motivation